AB0864 Pediatric Acute-Onset Neuropsychiatric Syndrome (PANS): Clinical Evaluation in A Group of Italian Children. A Different Entity from Pandas?. (15th July 2016) - Falcini, F.; Lepri, G.; Ferrari, A.; Matucci-Cerinic, M.; Meini, A.
Abstract : Background: PANDAS (Pediatric Autoimmune Neuropsychiatric Disorders associated with Streptococcal Infections) identifies a subgroup of pts with unusually abrupt and dramatic TIC/OCD onset GAS infection related. PANS "Pediatric acute-onset neuropsychiatric syndrome" is a term proposed to describe a clinically distinct presentation of OCD/TIC with post infectious origin. Differently from PANDAS, in PANS other agents may trigger the disease, including Mycoplasma pneumonia, Influenza viruses, Epstein Barr virus, Borrelia Burgdorferi, Herpes simplex and Varicella viruses. Clinical presentation is characterized by an abrupt dramatic onset of OCD and additional neuropsychiatric symptoms nor explained by known neurologic or medical disorders 1 . Objectives: To describe clinical features of 23 Italian children with OCD/TIC diagnosed as PANS in comparison to our PANDAS group. Methods: Between May 2009 through January 2016 we recruited 23 pts (13 M, 10 F) with OCD/TIC starting before puberty. The mean age at onset 77 mnths±35.6SD. Results: 19 (86.4%) were full-term born, 3 (13.6%) from Caesarean section (no information in 1 adopted child). 8/21 (38.1%) had familiars with OCD/tics or other neurologic diseases (2 pts without data). At onset, clinical signs were OCD in 3 (13%), OCD and motor tics in 7 (30.4%), motor tics in 5 (21.7%), vocal tics in 1 (4.3%), motor/vocal tics in 5 (21.7%), motor/vocal tics and OCD in 2 (8.7%), Mean age at diagnosis 106.8 months±36.9 SD. Antistreptolysin O and antiDNaseB titers were negative in all pts. In all EBV, Mycoplasma pneumoniae, CMV, Borrelia Burgdorferi were tested: 2 pts had history of tick bite and Borrelia Burgorferi Ab+, 6 pts Mycoplasma pneumoniae Ab+, 1 EBV Ab+; in 2 pts a VZV infectionAb+ was found. In 1 child Rotavirus infection was suspected and 12 had a viral pharyngitis before OCD/Tics onset. All underwent neuropsychiatric evaluation, none had deficit of psychological development; in all autoimmunity (ANA; antiDNA and ENA Ab) was negative as well as cerebral MR and EEG. All received antibiotic therapy according to the specific infection: pts with Mycoplasma macrolide, pts with VZV antiviral, pts with Borrelia amoxicillina. All showed benefit during and after the treatment. Pts, with no specific agent, received amoxicillina and benzathine benzylpenicillin with benefit after a more prolonged period than PANDAS pts. Conclusions: Our data show that PANS as PANDAS prediliges males with higher familiar predisposition in PANS. The age at onset is comparable to PANDAS, while OCD are more common and severe than in PANDAS. All pts had an infectious event, as PANDAS pts, but the trigger agent was different from GAS, and all responded to the specific therapy. PANDAS and PANS mainly differs from the trigger agent. The knowledge of PANS and PANDAS is mandatory to early recognize children at the disease onset avoiding to delay the diagnosis and the beginning of therapy. Acknowledgement: 1 Chang K et al. Clinical evaluation of Youth with pediatric acute onset neuropsychiatric syndrome (PANS): recommendations from the 2013 PANS Consensus Conference. J Child Adolescent Psychopharmacology 2015:25:3–13 Disclosure of Interest: None declared